The possible connection between neutrophil-to-high-density lipoprotein ratio and cerebral perfusion in clinically established corticobasal syndrome: a pilot study - Chunowski, Patryk; Migda, Bartosz; Madetko-Alster, Natalia; Migda, Anna; Kutyłowski, Michał; Królicki, Leszek; Alster, Piotr (Frontiers in Neurology, 2024)
Introduction Progressive supranuclear palsy (PSP) and corticobasal syndrome (CBS) are tauopathic atypical parkinsonisms. Given their overlap in terms of clinical manifestation, there is growing interest in the mechanisms leading to these entities. Materials and methods In total, 71 patients were included in the study, 19 of whom were clinically diagnosed with CBS, 37 with PSP, and 15 with Parkinson's disease (PD). The mean ages of the participants were 72.8, 72.9, and 64.0 years, respectively, and the disease duration varied from 3 to 6 years. Each individual underwent blood collection. Morphological and biochemical evaluation of blood samples was performed to analyze the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and neutrophil-to-high-density lipoprotein ratio (NHR). A single-photon emission computed tomography (SPECT) with technetium-99m hexamethylpropyleneamine oxime (99Tc-HMPAO) tracer was used to assess perfusion in two regions of interest (ROI): the thalamus and insula. Using Pearson correlation to assess the linear relationship between NHR and perfusion in the insula and thalamus for CBS, PSP, and PD patients, the authors intended to verify possible correlations between NLR, PLR, and NHR and perfusion in the indicated ROIs. Results The study revealed a negative linear correlation between NHR and perfusion of both the left (Insula L; R = −0.59) and right (Insula R; R = −0.58) insula regions. Similar to the insula, a linear correlation between NHR and activity in both the left (Thalamus L) and right (Thalamus R) thalamus regions in CBS subjects with a relatively stronger correlation in the right thalamus (R = −0.64 vs. R = −0.58) was found. These observations were not confirmed in PSP and PD patients. Conclusion Simultaneously using non-specific parameters for peripheral inflammation (NLR, PLR, and NHR) and perfusion, SPECT may be an interesting beginning point for further analysis of inflammatory disease mechanisms. To the best of our knowledge, this is the first study to address the potential correlation between the peripheral neuroinflammatory markers NLR, PLR, and NHR and perfusion disturbances in particular ROIs.